The Rise of Social Inequality in the 21st Century - Manav Thakur (Sampreshan, ISSN:2347-2979 UGC CARE Group 1, 2024)
Social inequality has been a persistent issue throughout human history, but it appears to be widening in the 21st century. This research paper will examine the factors that are contributing to the rise of social inequality, such as globalization, technological change, and the decline of labor unions. The paper will also explore the consequences of social inequality, both for individuals and for society as a whole. By analyzing relevant data and scholarly perspectives, this paper will aim to provide a nuanced understanding of the causes and effects of social inequality in the contemporary world.